خواتین کو نبوی ہدایات: عبادات سے متعلق احکام و فرامین کا مطالعہProphetic Instructions to Women: Studying the Directions and Advices related to Worship (Al-Qamar, 2021)
Islamic rules for men include women in general, but Islam also pays a special attention to addressing women in various matters. In the Quran and Prophetic traditions and directions, we find many instructions in which special attention is paid to the education of women. This article is the study of the commands and advices of the Prophet to women regarding worship, particularly concerning the pillars of Islam. It finds that the Prophet guided women in the issues related to Salāt, Zakā, Sawm and Ḥajj. These teachings to women about the mentioned forms of worship are a way to dispel misconceptions and Bidʻāt regarding ʻIbādāt.
Keywords: Women; worship; instructions